DEVELOPMENT OF THE E-BOOK MEDIA IN LEANIING ENGLISH READING SKILL FOR CLASS VIII AT SMP PGRI BAKUNG - Naim, Miftakhul; Saifudin, Ahmad; Rofi'ah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The research carried out by the researcher aims to describe and understand the process of developing ebook teaching media as learning reading media, especially in English language learning in class VIII semester 2 and also to determine the results of ebook media development in class VIII PGRI Bakung Junior High School, in accordance with the source of the problem that has been found, the limitations of learning media that result in students being less enthusiastic in participating in learning. This research is a qualitative study, the data collection technique used in this study is a saturated sampling technique with a sample of 12 students consisting of 5 boys and 7 girls, this study uses the ADDIE development model, this model was chosen because it is in accordance with the media development carried out by researchers. The instruments used in this study were questionnaires from media experts, material experts, and student response questionnaires. Based on the responses, the development of ebook media is quite effective, calculated from the validation of media experts showing a score of 85.0% from material experts and 97.5% from content experts. Meanwhile, the student response score was 89.5%. This shows that ebook learning media is suitable for use in learning